Analisis Hambatan Pemahaman Maharah Kitabah pada Pembelajaran Bahasa Arab Siswa Pesantren Tahfiz Darul Mafaza Deli Serdang - Abdurrahman Abdurrahman; Rifka Emiyiati; Rizkatul Amaliah Harahap; Muhammad Umair; Sahkholid Nasution (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Maharah Kitabah is the most urgent Arabic language skill in learning Arabic, this is because this skill is the peak that includes all other skills. So if students understand it, it will be easier for them to understand Arabic as a whole. In this case the author conducted research by analyzing the obstacles to learning the Maharah Kitabah. The aim of the research is to find out what obstacles or mistakes hinder students from improving their Arabic writing skills, especially at the Tahfiz Darul Mafaza Islamic Boarding School, Deli Serdang. By focusing this research on Maharah Al-Kitabah, efforts can be made to obtain good learning strategies, so that students' understanding will be much better and they will get solutions to the problems they face when writing Arabic language sequences. This research was conducted using a qualitative and descriptive approach. Students at the Tahfiz Darul Mafaza Islamic Boarding School in Deli Serdang face problems in Maharah Al-Kitabah, and this research aims to describe these errors and problems. Data are collected in natural environments and phenomena are interpreted using qualitative methods. Apart from that, to gain a better understanding of the problem being researched, the researchers used methods such as qualitative surveys and also used an analytical approach which the author quoted from various secondary data, in the form of scientific journals, theses and internet media.